RESPON KEDELAI (Gliycine max L. Merril) TERHADAP CAMPURAN KOMPOS TANDAN KOSONG KELAPA SAWIT, ABU BOILER DAN TRICHODERMA PADA GAWANGAN SAWIT BELUM MENGHASILKAN DI LAHAN GAMBUT - Rika Yunita; Nelvia ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to study the composition of the mixture of compost of oil palm empty fruit bunch (Compost of OPEFB), boiler ash and trichoderma on the growth aud yeilds of soybean (Glycine max L. Merrill) in oil palm plantations on peatlands. The experiment was conducted in the Kualu Nenas village, district of Kampar, Riau Province. Experiments used a randomized block design (RBD) consisting of 9 treatments, A (without treatment), B (1.56 kg compost of OPEFB)/plots, C (1.56 kg compost of OPEFB + 156 g boiler ash)/plots, D (1.56 kg compost of OPEFB + 312 g boiler ash)/plots, E (1.56 kg compost of OPEFB + 468 g boiler ash)/plots, F (1,56 kg compost of OPEFB + 3.12 g trichoderma)/plots, G (1.56 kg compost of OPEFB +156 g boiler ash + 3.12 g tichoderma)/plots, H (1.56 kg compost of OPEFB + 312 g boiler ash + 3.12 g trichoderma)/plots, I (1.56 kg compost of OPEFB + 468 g boiler ash + 3.12 g tichoderma)/plots each repeated three times. The parameters observed were plant height, number of primary branches, flowering age, number of pods, number of pods pithy, and dry seed weight per plot. The results show that the treatment of H (1.56 kg compost of OPEFB + 312 g boiler ash+3,12 g trichoderma)/plots increased of plan height, plowering age, number of pods, number of pods pithy, and dry seed weight per plot, significantly compared with no treatment, but not significant compared to the other treatments. Keywords: Soybean, peatpland, compost of OPEFB, boiler ash and trichoderma